2012
DOI: 10.1002/chem.201200576
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient D2 Generation by Dehydrogenation of Formic Acid in D2O through H+/D+ Exchange on an Iridium Catalyst: Application to the Synthesis of Deuterated Compounds by Transfer Deuterogenation

Abstract: Deuterated compounds have received increasing attention in both academia and industrial fields. However, preparations of these compounds are limited for both economic and practical reasons. Herein, convenient generation of deuterium gas (D(2)) and the preparation of deuterated compounds on a laboratory scale are demonstrated by using a half-sandwich iridium complex with 4,4'-dihydroxy-2,2'-bipyridine. The "umpolung" (i.e., reversal of polarity) of a hydrogen atom of water was achieved in consecutive reactions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
78
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 70 publications
7
78
0
Order By: Relevance
“…[41] First, the pH dependency of catalytic activity greatly varies depending on the substitution positions of the OH groups. [41] First, the pH dependency of catalytic activity greatly varies depending on the substitution positions of the OH groups.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[41] First, the pH dependency of catalytic activity greatly varies depending on the substitution positions of the OH groups. [41] First, the pH dependency of catalytic activity greatly varies depending on the substitution positions of the OH groups.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[41] First, the pH dependency of catalytic activity greatly varies depending on the substitution positions of the OH groups. [41] On the other hand, RDS of 3 was presumed to be (ii) by decrease of energy barrier of (iii) due to the pendant base effect of the OH group near the metal. On the other hand, the catalyst 3 showed the maximum TOF (entry 5, 5440 h −1 ) of the catalytic activity in a 1:1 mixed solution of FA/sodium formate (SF, pH 3.5).…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…10,[50][51][52] We have previously investigated the mechanism of formic acid dehydrogenation with KIE studies, 50 and demonstrated a significant effect depending on the specific ligands with or without pendent OHs in the complexes. Complexes with 6,6′-dihydroxy- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 6 2,2′-bipyridine (OH substituents in ortho positions) exhibit a different pH dependence than those with 4,4′-dihydroxy-2,2′-bipyridine (OH substituents in para positions) owing to the two classes of complexes having different rate determining steps (RDS) in the catalytic cycle.…”
mentioning
confidence: 99%
“…2,2'-Biimidazole was purc h a s e d f r o m S a n t a C r u z B i o t e c h n o l o g y, I n c . 2-( P y r i d i n e -2-y l ) -i m i d a z o [1,2-a ] p y r i d i n e 37) , 1-(pyridine-2-yl)imidazo[1,5-a]pyridine 38) , 3-(pyridine-2-yl)-imidazo[1,5-a]pyridine 39) , 4,4'-biimidazole 40), 41) , 1,1'-dimethyl-2,2'-biimidazole 42) , and [IrCp (H2O)3] [SO4] 43) were synthesized according to the respective literature procedures . Complexes 1a-b, 3, 4, 6, 10, and 12 were synthesized according to the literature 34) .…”
Section: Methodsmentioning
confidence: 99%